UTILITAS DALAM PERILAKU KONSUMEN PERSPEKTIF NILAI KEISLAMAN - Ainun Barakah (CENDEKIA: Jurnal Studi Keislaman, 2018)
Humans are social creatures that consist of two elements, namely self (lust) and soul (spirit), the first element is closely related to the physical while the second is related to mental / spiritual meaning. To measure the level of satisfaction as a consumer, three approaches were taken, namely utility approach, indefer curve approach and attribute approach. This paper will discuss consumer satisfaction using the total utility approach by comparing physical and non-physical satisfaction. The method used is descriptive qualitative, with data sources (library research), namely literature review sourced from several related literature, both from articles or classic books (turats).